Health Impact Assessment as a planning and decision-making tool - Jamal Hisham, Hashim; Mohammad Adam, Adman
Health impact assessment (HIA) is a versatile planning and decision-making tool that has been applied in many situations but more so in environmental impact assessment (EIA). In many developed and developing countries, many development activities and projects are now subjected to EIA. HIA in urban planning although limited, is now being increasingly applied, whereby the planning of a city including its transportation system and corridors can have significant health implications on city dwellers. This paper discusses the usefulness of HIA as an impact assessment tool in various applications including in urban planning. The International Finance Corporation (IFC) has introduced a comprehensive HIA which includes health risk assessment (HRA). Environmental HRA is a standardized characterization of potential negative health impacts resulting from human exposures to dangerous agents or circumstances within the environment. HIA as a planning and decision-making tool will become more universal in its applications.